Faktor-Faktor yang Berhubungan dengan Pemberian Asi Eksklusif di Wilayah Kerja Puskesmas Poasia Kota Kendari Provinsi Sulawesi Tenggara - Feryani, Feryani; Nursaidah, Nursaidah (Health Information : Jurnal Penelitian, 2018)
Breast milk (ASI) is the best source of nutrition for babies because it contains various nutrients needed in the growth and development of babies. Giving breast milk is highly recommended until the baby is 6 months old (Utami, 2005). Data on Exclusive Breastfeeding at Poasia Health Center in 2015 amounted to 77.07% and based on the results of surveys in several Posyandu in the Poasia Community Health Center working area, most of the visiting babies were given formula milk and complimentary food for breast milk. This shows that the practice of exclusive breastfeeding is still low which can affect the growth and development of infants so that it will affect the quality of human resources. Research Objectives: To find out the factors related to exclusive breastfeeding at Posyandu in the working area of Poasia Health Center, Kendari City, Southeast Sulawesi Province in 2016. Research methods: The research conducted was analytical research with an approach cross-sectional. The study sample was mothers who had babies aged 7 to 24 months in the working area of Poasia Health Center with a total of 77 people. The sampling technique is an accidental sampling. The results of the study: the results of this study were the education of mothers who gave exclusive breastfeeding 80.8% of secondary education (SMA) mothers and those who did not provide exclusive breastfeeding 100% of mothers with higher education. Employment of mothers who provide exclusive breastfeeding 54.8% of working mothers and those who do not provide exclusive breastfeeding 100% of working mothers. The parity of mothers who gave exclusive breastfeeding was 67.7% in mothers with no risk (parity 2-3) and those who did not give exclusive breastfeeding 58.7% in mothers at risk parity (parity 1 and 4), and there was a relationship between education, employment and maternal parity with exclusive breastfeeding in the working area of Kendari City Poasia Health Center with a value of value <0.05.